Is Dunbar's number up? - Wellman, Barry (The British journal of psychology, 2012)
This article is a commentary on 'Relationships and the social brain: Integrating psychological and evolutionary perspectives' (Sutcliffe, Dunbar, Binder, & Arrow, 2012). Adapted from the source document.